Pengembangan Gim Edukasi Mengetik menggunakan Metode Touch-Typing untuk Meningkatkan Kecepatan Mengetik - Muhammad Wahyu Pamengas; Tri Afirianto; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Typing skill is an important ability to have in modern times. According to Norb Winslow, the average typing speed of adults (classified as beginners) is 30 WPM, while the average typing speed for those who use the keyboard quite often (intermediates) is 40 WPM. The problem is, the minimum typing speed required for efficient work is 40 WPM. One way to increase typing speed is by practicing touch-typing techniques. The typist's focus remains on the reading source and at the same time typing it. Users of this technique use muscle memory to determine the position of each key on the keyboard. With this technique, the typist does not need to look at the keyboard when typing, so the typing speed becomes faster. This research aims to develop an educational game that can help improve typing speed. The game is developed using the DGBL-ID model and the drill method is used as a learning method in the game. Testing is done by observing three respondents who have been selected using convenience sampling. The results of the test analysis show that there is a positive impact of the use of game on player's typing speed.